Identification of CCZ1 as an essential lysosomal trafficking regulator in Marburg and Ebola virus infections - Monteil, Vanessa; Kwon, Hyesoo; John, Lijo; Salata, Cristiano; Jonsson, Gustav; Vorrink, Sabine U.; Appelberg, Sofia; Youhanna, Sonia; Dyczynski, Matheus; Leopoldi, Alexandra; Leeb, Nicole; Volz, Jennifer; et al. (Nature communications, 2023)
Marburg and Ebola filoviruses are two of the deadliest infectious agents and several outbreaks have occurred in the last decades. Although several receptors and co-receptors have been reported for Ebola virus, key host factors remain to be elucidated. In this study, using a haploid cell screening platform, we identify the guanine nucleotide exchange factor CCZ1 as a key host factor in the early stage of filovirus replication. The critical role of CCZ1 for filovirus infections is validated in 3D primary human hepatocyte cultures and human blood-vessel organoids, both critical target sites for Ebola and Marburg virus tropism. Mechanistically, CCZ1 controls early to late endosomal trafficking of these viruses. In addition, we report that CCZ1 has a role in the endosomal trafficking of endocytosis-dependent SARS-CoV-2 infections, but not in infections by Lassa virus, which enters endo-lysosomal trafficking at the late endosome stage. Thus, we have identified an essential host pathway for filovirus infections in cell lines and engineered human target tissues. Inhibition of CCZ1 nearly completely abolishes Marburg and Ebola infections. Thus, targeting CCZ1 could potentially serve as a promising drug target for controlling infections caused by various viruses, such as SARS-CoV-2, Marburg, and Ebola. Host factors involved in filovirus infection are incompletely understood. Here, the authors used a haploid cell screening system to unveil CCZ1’s crucial role in regulating endosomal trafficking thus virus movement within cells and thereby impacting Marburg and Ebola infection.